Self-perceived physical fitness and occurrences of individual levels of autistic traits in adolescents: a cluster association study - Vanilson Batista Lemes; Anelise Reis Gaya; Jorge Mota; Caroline Brand (BMC Psychiatry)
Abstract Background The association between physical fitness and autistic traits in adolescents remains under explored, especially in adolescents. Understanding this relationship can provide strategies to improve the quality of life of these people. Objective To identify the association between cluster characteristics derived from levels of self-perceived physical fitness and the occurrences of individual levels of autistic traits in Brazilian adolescents. Method This descriptive study employed an analytical, quantitative approach involving 515 adolescents aged 11 to 18 (245 boys and 270 girls). Autistic traits were assessed using the Autism Quotient (AQ50), while physical fitness was measured with the Self-Reported Physical Fitness Questionnaire (QAPA). Cluster analysis using descriptive statistics with bootstrapping and generalized estimating equations was performed. Results Boys reported higher physical fitness levels than girls, with significant differences in General Power Strength (QAPA 4) and Physical Fitness in Sports (QAPA 7). Girls scored slightly higher on social skills. AQ50 scores indicated that girls had higher aggregated difficulties in imagination, attention, communication, and social skills compared to boys. Higher self-perceived physical fitness was associated with lower levels of autistic traits in both genders. Girls with higher QAPA scores showed significant decreases in autistic traits related to social skills and overall AQ50 scores. Boys with higher physical fitness demonstrated reduced autistic traits in the domains of imagination and communication. Age-adjusted analyses confirmed these findings. Conclusion There is a significant association between self-perceived physical fitness and autistic traits in adolescents. Higher physical fitness levels are linked to fewer autistic traits, highlighting the importance of promoting physical fitness to mitigate challenges associated with autistic traits and improve adolescents' well-being.